Recent Publications (Quarterly Journal of Economics, 1966)
Recent Publications Get access The Quarterly Journal of Economics, Volume 80, Issue 2, May 1966, Pages 337–341, https://doi.org/10.1093/qje/80.2.337 Published: 01 May 1966